A case study from a Japanese flipped engineering research course. (2016) - Hirata, Yoshihiro
This study describes a process of testing a flipped teaching approach in ongoing graduate research classes given in an engineering course in a Japanese university. At the beginning of the course, students were required to brainstorm their ideas on their projects and make research plans outlining them. Four months later, they were required to give biweekly presentations about their progress towards their final presentations. This study explores the effectiveness of an approach, which requires students in advance of class to watch video-recorded instructions created by the instructor. It also examines the benefits and drawbacks of instructors' customisation of the flipped teaching approach and updates on students' progress.